ESE audit on management of adult growth hormone deficiency in clinical practice. Issue 2 (February 2021) - Martel-Duguech, Luciana; Jorgensen, Jens Otto L; Korbonits, Márta; Johannsson, Gudmundur; Webb, Susan M; ,
Abstract : Guidelines recommend adults with pituitary disease in whom GH therapy is contemplated, to be tested for GH deficiency (AGHD); however, clinical practice is not uniform. Aims: (1) To record current practice of AGHD management throughout Europe and benchmark it against guidelines; (2) To evaluate educational status of healthcare professionals about AGHD. Design: Online survey in endocrine centres throughout Europe. Patients and methods: Endocrinologists voluntarily completed an electronic questionnaire regarding AGHD patients diagnosed or treated in 2017–2018. Results: Twenty-eight centres from 17 European countries participated, including 2139 AGHD patients, 28% of childhood-onset GHD. Aetiology was most frequently non-functioning pituitary adenoma (26%), craniopharyngioma (13%) and genetic/congenital midline malformations (13%). Diagnosis of GHD was confirmed by a stimulation test in 52% (GHRH+arginine: 45%; insulin-tolerance: 42%, glucagon: 6%; GHRH alone and clonidine tests: 7%); in the remaining, ≥3 pituitary deficiencies and low serum IGF-I were diagnostic. Initial GH dose was lower in older patients, but only women <26 years were prescribed a higher dose than men; dose titration was based on normal serum IGF-I, tolerance and side-effects. In one country, AGHD treatment was not approved. Full public reimbursement was not available in four countries and only in childhood-onset GHD in another. AGHD awareness was low among non-endocrine professionals and healthcare administrators. Postgraduate AGHD curriculum training deserves being improved. Conclusion: Despite guideline recommendations, GH replacement in AGHD is still not available or reimbursed in all European countries. Knowledge among professionals and health administrators needs improvement to optimise the care of adults with GHD.